Implementation and control for current distribution in quadratic boost converters connected in parallel - Ong, Jun Kang (Nanyang Technological University, 2023)
With the future looking towards renewable energy, Solar Photovoltaic is one of the solutions available. However, to be able to integrate it into our everyday lives, a converter is required to amplify the power absorbed by natural means to a level usable by consumers. Hence, this project aims to explore the possibility of increasing the efficiency of Solar Photovoltaic in terms of its response time.